2014
DOI: 10.1016/j.neuropsychologia.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic response of children with attention-deficit and hyperactive disorder (ADHD) to emotional facial expressions

Abstract: a b s t r a c tChildren with attention-deficit/hyperactivity disorder (ADHD) have difficulty recognizing facial expressions. They identify angry expressions less accurately than typically developing (TD) children, yet little is known about their atypical neural basis for the recognition of facial expressions. Here, we used nearinfrared spectroscopy (NIRS) to examine the distinctive cerebral hemodynamics of ADHD and TD children while they viewed happy and angry expressions. We measured the hemodynamic responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 52 publications
(82 reference statements)
9
38
1
1
Order By: Relevance
“…Previous work found that children with ADHD have greater difficulty identifying emotional stimuli, especially negative ones [37, 39, 77]. The current findings may shed light onto the notion that inhibitory control in children with ADHD is particularly susceptible in negatively loaded circumstances.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Previous work found that children with ADHD have greater difficulty identifying emotional stimuli, especially negative ones [37, 39, 77]. The current findings may shed light onto the notion that inhibitory control in children with ADHD is particularly susceptible in negatively loaded circumstances.…”
Section: Discussionsupporting
confidence: 61%
“…Children and adolescents with ADHD experience deficits in processing emotional content [3338], particularly stimuli with angry valence [39, 40]. Further, childhood hot EF is considered a fairly stable trait [41] that has been related to long-term deficits in interpersonal relations [42] and stress mismanagement [43].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed hypoactivation in the right frontal lobe including the prefrontal cortex (PFC; Xiao et al, 2012; Yasumura et al, 2014), middle frontal gyrus (MFG), and inferior frontal gyrus (IFG) (Monden et al, 2012, 2015; Nagashima et al, 2014a,b,c), presumably because NIRS probes can easily be applied to the frontal region (see Table 1). These studies also found hypoactivation in the temporal (Ichikawa et al, 2014; Köchel et al, 2015) and parietal cortices (Nagashima et al, 2014b) as well.…”
Section: Lateralization In Atypical Neural Function In Adhdmentioning
confidence: 87%
“…Most of the studies of children with ADHD show atypical patterns of oxyHb more prominently in the right hemisphere during a variety of tasks such as the reverse-Stroop task (Yasumura et al, 2014), executive attention control task (Tsujimoto et al, 2013), verbal fluency task (VFT; Schecklmann et al, 2009), Go/NoGo task (Monden et al, 2012, 2015; Xiao et al, 2012; Nagashima et al, 2014a), oddball task (Nagashima et al, 2014b,c), passive viewing of facial expression (Ichikawa et al, 2014), and emotional prosody recognition (Köchel et al, 2015). These studies have revealed hypoactivation in the right frontal lobe including the prefrontal cortex (PFC; Xiao et al, 2012; Yasumura et al, 2014), middle frontal gyrus (MFG), and inferior frontal gyrus (IFG) (Monden et al, 2012, 2015; Nagashima et al, 2014a,b,c), presumably because NIRS probes can easily be applied to the frontal region (see Table 1).…”
Section: Lateralization In Atypical Neural Function In Adhdmentioning
confidence: 99%
“…The children with ADHD did not exhibit cortical activity while watching angry faces, which illustrates the impairment of ADHD children to recognize an angry face. 62 Using a¯ve-fold crossvalidation in an SVM-based classi¯cation of 24 channels of fNIRS data proved to be fruitful in achieving a maximum accuracy of 84% in di®erentiating between patients with ADHD and those with ASD. 19 Neurofeedback training using a visual display yielded good results as it reportedly reduced the ADHD symptoms in children.…”
Section: Visual Taskmentioning
confidence: 99%